2021
DOI: 10.1155/2021/9985185
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Improvement and Optimization of Feature Selection Algorithm in Swarm Intelligence Algorithm Based on Complexity

Abstract: The swarm intelligence algorithm simulates the behavior of animal populations in nature and is a new type of intelligent solution that is different from traditional artificial intelligence. Feature selection is a very common data dimensionality reduction method, which requires us to select the feature subset with the best evaluation criteria from the original feature set. Feature selection, as an effective data processing method, has become a hot research topic in the fields of machine learning, pattern recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In recent decades, with the maturity of AI technology, some of its research results have been successively applied to the field of teaching, which has promoted the process of educational development reform and teaching modernization [8]. It is the most important resource for the development of education, so the development of teachers has always been paid attention to, and our country will also take comprehensively deepening the construction of teachers as the focus of education [9]. With the rapid development of big data, cloud computing, AI, and other technologies, new requirements are put forward for the development of teachers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, with the maturity of AI technology, some of its research results have been successively applied to the field of teaching, which has promoted the process of educational development reform and teaching modernization [8]. It is the most important resource for the development of education, so the development of teachers has always been paid attention to, and our country will also take comprehensively deepening the construction of teachers as the focus of education [9]. With the rapid development of big data, cloud computing, AI, and other technologies, new requirements are put forward for the development of teachers.…”
Section: Introductionmentioning
confidence: 99%
“…In (2) shows the light intensity of the firefly. Where the absorption coefficient is denoted by γ and the initial value is denoted by (I0) at (r=0) [19]- [21].…”
Section: Methods 21 Research Specificationmentioning
confidence: 99%
“…Based on several predetermined specifications, steps were developed to test the performance of Arduino Uno in optimization using this FFA, starting with initializing initial conditions for the basic parameters of the FFA (γ, α, n, iterations, and β). These parameters are started to be generated based on the initial conditions according to (2). FFA started to work on calculating the light intensity and evaluating the weight of each firefly population according to (3) and ( 4).…”
Section: Research Stagesmentioning
confidence: 99%
“…The experiments showed that, under the feature selection algorithm, students' academic performance was approximately 30% greater than the other methods of teaching, and the sense of cooperation among students reached 0.8. The contradiction between popularity and improvement was solved, and the problem of differentiation and transformation of late-comers was solved [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…To verify the data enhancement results of the characteristic choice alcohol system, which is based on the group smart algorithm, Chen et al conducted experiments in six classes with similar conditions in the first middle school of the city. e experiments showed that, under the feature selection algorithm, students' academic performance was approximately 30% greater than the other methods of teaching, and the sense of cooperation among students reached 0.8. e contradiction between popularity and improvement was solved, and the problem of differentiation and transformation of late-comers was solved [9].…”
Section: Related Workmentioning
confidence: 99%